Особливості мотивування працівників митних органів - Ганас, Л. М.; Дорош, О. І.; Білець, Л. В.; Hanas, L. M.; Dorosh, O. I.; Bilec, L. V. (Видавництво Львівської політехніки, 2020)
Ґрунтовно проаналізовано інструменти мотивування працівників митниці, описано основні види матеріальних і нематеріальних стимулів, які застосовують щодо працівників митних органів, та порядок їх застосування. Визначено також інструменти демотивування як важливі складові управління персоналом та надано рекомендації щодо покращення системи мотивування задля підвищення мотивації митників і збільшення їхньої трудової активності.

The problem of quality performance by employees of their duties always arises before managers of different enterprises. Sometimes this problem is solved at certain stages in the life cycle of companies, but work of motivating of staff is continuing constantly. Today, a variety of employee motivation techniques are available, based on a number of theories. But the needs of employees are increasing, changing, priorities and emphasis are shifting, so long-term using of similar approaches is ineffective. It is much more difficult to motivate government officials, where changes in incentives should be clearly regulated. One of these structures is the State Customs Service of Ukraine, which is undergoing reform. The formation of a new customs office can not be without changes in the approaches to employee motivation. In order for the customs authorities to successfully fulfill their duties, they must have sufficient motivation. However, to date, the system of customs officials motivation in Ukraine is imperfect and needs immediate changes, which leads to the relevance of the topic. The dominant purpose of this paper is to determine the characteristics of the motivation of customs authorities and to provide theoretical recommendations to increase their level of motivation to improve work activity. The article thoroughly analyzes the instruments of motivation of customs officers, describes the main types of tangible and intangible incentives that are applied to customs officials and the procedure for their application. It also identifies tools for demotivation as important components of human resource management and provides recommendations for improving the motivation system to increase the motivation of customs officers and increase their employment. According to the results of the research, it can be concluded that the system of motivation of customs authorities is quite wide, since tangible and intangible incentives for work are actively used, as well as the process of employee demotivation. However, at the same time, this system is imperfect, since very little attention is paid to the self-development of workers, the realization of their creative abilities and personal qualities. Employees should be given the opportunity to learn, progress, encourage and develop their creative potential. This can be done through special training seminars, advanced training courses, using sports hours, team building etc. Forms and pay systems should also be reviewed.
Features of motivation of customs authorities
Keywords: Державна митна служба України; митні органи; митник; мотивування; мотивація; теорії мотивування; стимул; State Customs Service of Ukraine; customs authorities; customs officer; motivation process; motivation; theories of motivation; incentive; 339.543